The role of the teaching assistant: Female role models in the classroom. (December 2021) - Griffith, Amanda L.; Main, Joyce B.
Highlights: We examine the impact of a gender match for female students and teaching assistants (TA) for an introductory engineering course on grades and major choice. Female students matched with a female TA are more likely to choose one of the highest-earning fields within engineering than if their TA is male. We provide some evidence that this effect is more pronounced when the female presence in the classroom is larger (female instructor, more female peers). We do not find evidence that matching with a female TA improves female student grades. Abstract: We use a dataset of first-year engineering students from a selective research-intensive public university to examine the impact of same-gender teaching assistants on course grades and major field choice. Our sample consists of students who were randomly assigned to a section of an introductory engineering course and a graduate teaching assistant. Results suggest there may be small positive effects on course grades and the probability of majoring in a high-earning field for female students assigned to a female teaching assistant. Although the difference is marginally significant, the impact of a teaching assistant gender match for female students' choice of a high-earning field is more pronounced in classrooms with a female instructor and above-median representation of female peers. Our results show limited evidence that female teaching assistants can provide the same benefits of a female instructor in STEM fields.